2011
DOI: 10.1029/2010jc006525
|View full text |Cite
|
Sign up to set email alerts
|

Observed and modeled bio-optical, bioluminescent, and physical properties during a coastal upwelling event in Monterey Bay, California

Abstract: [1] During spring and summer time, coastal upwelling influences circulation and ecosystem dynamics of the Monterey Bay, California, which is recognized as a National Marine Sanctuary. Observations of physical, bio-optical properties (including bioluminescence) together with results from dynamical biochemical and bioluminescence models are used to interpret the development of the upwelling event during August 2003 in Monterey Bay, California. Observations and the biochemical model show the development of a phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 30 publications
(49 reference statements)
0
27
1
Order By: Relevance
“…Non‐bioluminescent phytoplankton were advected. Results from the dynamical bioluminescence model showed high values of bioluminescence intensity (BL) along the entrance to the Bay [ Shulman et al , 2011], which was not in agreement with the observed BL. In the model, the BL dynamics were controlled by advective and diffusive processes only, and as it was speculated by Shulman et al [2011], the lack of modeling of behavioral dynamics of bioluminescent organisms, as well as modeling of growth and loss terms, are responsible for the BL model's inability to predict the observed weakening of the BL intensity along the entrance to the Bay.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐bioluminescent phytoplankton were advected. Results from the dynamical bioluminescence model showed high values of bioluminescence intensity (BL) along the entrance to the Bay [ Shulman et al , 2011], which was not in agreement with the observed BL. In the model, the BL dynamics were controlled by advective and diffusive processes only, and as it was speculated by Shulman et al [2011], the lack of modeling of behavioral dynamics of bioluminescent organisms, as well as modeling of growth and loss terms, are responsible for the BL model's inability to predict the observed weakening of the BL intensity along the entrance to the Bay.…”
Section: Introductionmentioning
confidence: 99%
“…The Monterey Bay model (see domain in Figure ) consists of a physical model, which is coupled to a biochemical model (Shulman et al, ). The physical model of the Monterey Bay is based on the NCOM model, which is a primitive‐equation, 3‐D, hydrostatic model.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, in the field, bioluminescence has been used to study ecological dynamics within the plankton and to monitor toxic blooms (Moline et al, 2009;Shulman et al, 2011;Le Tortorec et al, 2013). Studies on dinoflagellate bioluminescence have shed like on fundamental processes like cellular mechanotransduction (von Dassow & Latz, 2002;Chen et al, 2007;Jin et al, 2013), circadian rhythms (Hastings, 2009) and evolution of gene structure (Liu et al, 2004;Liu & Hastings, 2007).…”
Section: Referencesmentioning
confidence: 99%